Children Receiving Hematopoietic Stem Cell Transplantation are at Increased Risk of Onychocryptosis Requiring Surgical Management. Issue 7 (October 2017) - Ezekian, Brian; Englum, Brian R.; Gilmore, Brian F.; Kim, Jina; Leraas, Harold J.; Driscoll, Timothy A.; Tracy, Elisabeth T.; Rice, Henry E.
Abstract : Purpose: At our institution, a high proportion of children with onychocryptosis (ingrown toenail) requiring surgical intervention were noted to have a history of hematopoietic stem cell transplantation (HSCT). We analyzed the characteristics of patients who underwent surgical intervention for onychocryptosis and examined our institutional HSCT database to determine if an association exists between onychocryptosis and HSCT. Materials and Methods: Surgical cases for onychocryptosis performed from 2000 to 2012 were identified. Nine demographic, clinical, and perioperative variables for both patients with and without prior HSCT were assessed. In a separate analysis, the institutional HSCT database was then queried to identify the prevalence and clinical characteristics associated with onychocryptosis after HSCT. Results: We identified 17 children who had undergone surgical management of onychocryptosis, of which 8 (47.1%) had previous HSCT. Children who had undergone HSCT had an aggressive form of onychocryptosis with 50.0% having bilateral great toe and nail edge involvement and 37.5% having a recurrence. In HSCT cohort analysis of 1069 children, 91 (8.5%) had onychocryptosis. Male sex, non-black race, acute graft versus host disease, and increasing age at transplantation were independently associated with onychocryptosis. Conclusions: HSCT is strongly associated with onychocryptosis requiring surgical intervention. Children with a history of HSCT may also have more aggressive toenail disease, with higher rates of surgical intervention, bilateral ingrown toenails, recurrence, and need for return to the operating room. Clinicians should perform careful screening and early treatment in these patients.